ITO layers modified in glow discharge plasma for Nematic Liquid Crystal alignment - Kolomzarov, Yu.; Oleksenko, P.; Rybalochka, A.; Sorokin, V.; Tytarenko, P.; Zelinskyy, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Influence of ionic and plasma treatment on orienting properties of indium-tinoxide (ITO) films was investigated. The stable tilt angle generation of nematic liquid crystal (NLC) molecules was attended. Dependences of NLC molecules tilt angles on various technological parameters and regimes of ITO film deposition have been shown. Results for oriented film surfaces investigated by atomic-force microscopy showed the viscous-elastic mechanism of NLC molecules alignment by the modified ITO films..